Not innocent enough: state compensation for miscarriages of justice in England and Wales - Hoyle, C; Tilt, L (Sweet and Maxwell, 2019)
This article discusses the changing landscape of statutory compensation for victims of miscarriages of justice in England and Wales, in light of the recent legislative challenge, R. (on the application of Hallam & Nealon) v Secretary of State for Justice. We argue that the Supreme Court's limited interpretation of the application of the presumption of innocence beyond criminal proceedings, and its conclusion that the statutory wording in s. 133 of the Criminal Justice Act 1988 is compatible with art. 6(2), places a near impossible burden on applicants for statutory compensation that is impractical and denies protection to those who have been let down by the State.